Risk and decision analysis of dynamic spectrum access. Issue 5 (June 2017) - Cui, Liu; Weiss, Martin B.H.; Morel, Benoit; Tipper, David
Abstract: Considerable research and policy development work has been conducted to construct methods and frameworks for ever denser sharing of radio spectrum. Since spectrum sharing necessarily constitutes a rearrangement of rights among stakeholders, considerable focus has been on examining the risks and incentives for license holders. But for spectrum sharing to be successful, it is critical to consider the incentives and risk for the entrants as well. This problem is challenging because the entrants are emergent entities that often do not participate in the policy or research debates. Because of this diversity, it is difficult to consider incentives, so this paper focuses instead on the risks faced by spectrum entrants and their mitigation. With clear understanding of risk and mitigation strategies associated, spectrum entrants can choose the method that maximize their utilities.